Deficiency of Angiotensinogen in Hepatocytes Markedly Decreases Blood Pressure in Lean and Obese Male Mice. Issue 4 (October 2015) - Yiannikouris, Frederique; Wang, Yu; Shoemaker, Robin; Larian, Nika; Thompson, Joel; English, Victoria L.; Charnigo, Richard; Su, Wen; Gong, Ming; Cassis, Lisa A.
Abstract : We recently demonstrated that adipocyte deficiency of angiotensinogen (AGT) ablated high-fat diet–induced elevations in plasma angiotensin II (Ang II) concentrations and obesity-hypertension in male mice. Hepatocytes are the predominant source of systemic AGT. Therefore, in this study, we defined the contribution of hepatocyte-derived AGT to obesity-induced elevations in plasma AGT concentrations and hypertension. Male Agt fl/fl mice expressing albumin-driven Cre recombinase were bred to female Agt fl/fl mice to generate Agt fl/fl or hepatocyte AGT–deficient male mice ( Agt Alb ). Mice were fed a low-fat or high-fat diet for 16 weeks. Hepatocyte AGT deficiency had no significant effect on body weight. Plasma AGT concentrations were increased in obese Agt fl/fl mice. Hepatocyte AGT deficiency markedly reduced plasma AGT and Ang II concentrations in lean and obese mice. Moreover, hepatocyte AGT deficiency reduced the content and release of AGT from adipose explants. Systolic blood pressure was markedly decreased in lean (by 18 mm Hg) and obese Agt Alb mice (by 54 mm Hg) compared with Agt fl/fl controls. To define mechanisms, we quantified effects of Ang II on mRNA abundance of megalin, an AGT uptake transporter, in 3T3-L1 adipocytes. Ang II stimulated adipocyte megalin mRNA abundance and decreased media AGT concentrations. These results demonstrate that hepatocytes are the predominant source of systemic AGT in both lean and obese mice. Moreover, reductions in plasma angiotensin concentrations in obese hepatocyte AGT–deficient mice may have limited megalin-dependent uptake of AGT into adipocytes for the production of Ang II in the development of obesity-hypertension. Abstract : Supplemental Digital Content is available in the text.